Upaya Meningkatkan Aktivitas Belajar Siswa Dengan Model Pembelajaran Kooperatif Tipe Stad (Student Team Achivement Division) Pada Mata Pelajaran Fisika Kelas XI IPA SKM 2 SMA Negeri 2 Payakumbuh - Erwin Satriadi (PAKAR Pendidikan, 2014)
The aim of this classroom action research is to increasen students learning activities and students learning achievement on physics. This research was done in two rounds. The research subject was the students from XI SKM 2 class, SMAN 2 Payakumbuh. The data in this study was collected by using questionare about students learning process activities and test. Data were analyzed by using quantitative qualitative technique. The result showed that: 1) Students ability in oral activities, motor activities, mental activities and emotional activities is still in the average category 2) The increase of student’s visual, listening, writing, and drawing activities happened in a low category 3) The using of cooperative learning model in STAD type can increase students achievements on basic competence.